Melvillian Meditations in Charles Johnson’s “Executive Decision” - Ženíšek, Jakub (American & British Studies Annual, 2020)
Regardless of its philosophical para-text, an overt reading of Charles Johnson’s short story “Executive Decision” suggests very obvious ideological connotations. The story displays the racial pride and black agency along with the ideologically loaded either-or antithesis of a competition between a white woman and a black man within a protracted job interview. At one point, the story even lapses into a sociological exposé. However, Johnson’s intertextual pairing of the story with Melville’s “Bartleby the Scrivener” significantly enhances its allusive potential, thereby redeeming the formulaic template of racial melodrama which Johnson frequently criticizes. By casting the African American character as a stand-in for Bartleby, the story opens up its narrow concern (affirmative action) to the larger theme of redistributive justice and the dangers of self-entitlement. In an eclectic reading, the story can even signify on the scarcity of positive male African American role models in the public eye, a theme which Johnson is very much preoccupied with.